Level of physical activity and the occurrence of chronic diseases in patients of the public healthcare system in presidente Prudente-SP - Da Costa Trindade, Ana Carolina Alves [UNESP]; Araujo, Monique Yndawe Castanho [UNESP]; Rocha, Ana Paula Rodrigues [UNESP]; Gobbo, Luís Alberto [UNESP]; Codogno, Jamile Sanches [UNESP] (Universidade Estadual de Maringa, 2016)
Aging is associated with a higher prevalence of chronic diseases, which can be minimized by a healthy and active lifestyle. The aim of this study was to analyze the occurrence of chronic diseases in Public Healthcare System patients, according to the level of physical activity. In total 542 patients, 29.7% (n = 161) male and 70.3% (n = 381) female, were evaluated in two Basic Health Units. The level of physical activity, presence of diseases and economic condition were verified through the use of questionnaires. Obesity was assessed using the Body Mass index (in kg/m2). Cardiac arrhythmia diseases (p = 0.033), arthritis/osteoarthritis (p = 0.010) and a herniated disc (p = 0.006) were associated with the level of physical activity. It is concluded that the level of physical activity is associated with the occurrence of chronic diseases in patients over the age of 50 years served by the Public Healthcare System of Presidente Prudente/SP city.
Keywords: Chronic diseases; Physical activity; Public Healthcare System